Exposure to environmental air pollutants as a risk factor for primary Sjögren’s syndrome - Ma, Kevin Sheng-Kai; Wang, Li-Tzu; Chong, Weikun; Lin, Cheng-Li; Li, Hailang; Chen, Aimin; Wei, James Cheng-Chung (Frontiers in Immunology, 2023)
Environmental etiology of primary Sjögren's syndrome (pSS), an autoimmune disease, has been proposed. This study determined whether the exposure to air pollutants was an independent risk factor for pSS. Participants were enrolled from a population-based cohort registry. Monthly average concentrations of air pollutants from 2000 to 2011 were divided into 4 quartiles. Adjusted hazard ratios (aHRs) of pSS for exposure to air pollutants were estimated in a Cox proportional regression model adjusting for age, sex, socioeconomic status, and residential areas. A subgroup analysis stratified by sex was conducted to validate the findings. Windows of susceptibility indicated years of exposure which contributed the most to the observed association. Ingenuity Pathway Analysis was used to identify underlying pathways of air pollutant-associated pSS pathogenesis, using Z-score visualization. Two hundred patients among 177,307 participants developed pSS, with a mean age of 53.1 years at a cumulative incidence of 0.11% from 2000 to 2011. Exposure to carbon monoxide (CO), nitric oxide (NO), and methane (CH4) was associated with a higher risk of pSS. Compared to those exposed to the lowest concentration level, the aHRs for pSS were 2.04 (95%CI=1.29-3.25), 1.86 (95%CI=1.22-2.85), and 2.21 (95%CI=1.47-3.31) for those exposed to high levels of CO, NO, and CH4, respectively. The findings persisted in the subgroup analysis, in which females exposed to high levels of CO, NO, and CH4 and males exposed to high levels of CO were associated with significantly high risk of pSS. The cumulative effect of air pollution on pSS was time-dependent. The underlying cellular mechanisms involved chronic inflammatory pathways including the interleukin-6 signaling pathway. Exposure to CO, NO, and CH4 was associated with a high risk of pSS, which was biologically plausible.